City mouse-country mouse and two more mouse tales from Aesop - Wallner, John, 1945-; Aesop (New York : Scholastic Inc., 1987)
City mouse-country mouse -- The lion and the mouse -- Belling the cat.
Keywords: Fables; Mice -- Folklore; Folklore